Earthquake and structural monitoring system (ENSMS) - Raja Ali, Raja Norasyikin (2008)
One main problem of earthquake prone countries is to own an earthquake sensor system. This is due to the expensiveness of the said item. Besides, the system itself is quite complicated and makes early detection of earthquake difficult. As such, a multi fuction and user friendly device has been invented under the project called Earthquake and Strustural Monitoring System (EnSMS). The system are complete with combinations of two devices namely seismograph for seismologist use and accelerograph widely used by building engineers. The new system is far cheaper than earlier available devices. Furthermore, its simple programming language and huge information storage could appeal to a wider usage of the device not only as a tool for earthquake detection but also a telecommunication channel to engineers and public.